Daud Beureu’eh and The Darul Islam Rebellion in Aceh - Apipudin Apipudin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2016)
AbstractThis paper seeks to explore the Darul Islam rebellion in Aceh under the leadership of Daud Beureu’eh, particularly the main factors which instigated the rebellion, the dynamics which took place during the rebellion, and the end of the rebellion. The Darul Islam rebellion in Aceh occurred because of several factors. Firstly, the people of Aceh were disappointed with the central government of Indonesia which failed to fulfill its promise to grant Aceh special autonomy. Secondly, there was a clash between the ulemas (Moslem clerics) faction who supported the autonomy and the uléëbalangs (customary leaders) who opposed the autonomy because they did not want the ulemas to assume dominance in the government of Aceh. Third, the Indonesian central government at that time was adopting a parliamentary system which was highly unstable and inconsistent in its perspective on and treatment of Aceh. The Darul Islam rebellion in Aceh is considered unique in that it did not claim as many lives as other Darul Islam rebellions in various regions throughout Indonesia. This rebellion effectively ended on May 8, 1962. In order to bring this conflict to a speedy end, the central government gave up military operations and sought for political settlement andamicable dialogues with DI/TII to reach a consensus concerning the Aceh problem. Peace in Aceh was secured after the central government decided to grant Aceh the status of Daerah Istimewa (Special Region), which meant that Aceh was given the right to exercise a special autonomy in the areas of religion, education, and tradition.—Abstrak Tulisan berusaha menjelaskan tentang pemberontakan Darul Islam pimpinan Daud Beureu’eh di Aceh, terutama terkait dengan faktor utama pemicu terjadinya pemberontakan, dinamika, dan akhir dari pemberontakan tersebut. Pemberontakan Darul Islam di Aceh terjadi karena beberapa faktor. Pertama, rakyat Aceh merasa bahwa pemerintah pusat Indonesia tidak menepati janjinya untuk memberikan otonomi khusus buat Aceh. Kedua, adanya pertentangan antara ulama yang mendukung status otonomi dan ulibalang yang menentang otonomi karena mereka tidak menginginkan ulama menjadi dominan dalam pemerintahan Aceh. Ketiga, pemerintah pusat Indonesia saat itu menerapkan sistem pemerintahan parlementer yang ternyata menciptakan ketidakstabilan dan inkonsistensi dalam memperlakukan Aceh. Pemberontakan Darul Islam di Aceh dianggap unik dibandingkan dengan pemberontakan Darul Islam di daerah yang lain di Indonesia. Pemberontakan ini berakhir pada tanggal 8 Mei 1962. Agar konflik ini segera berakhir, pemerintah pusat menghentikan operasi militer dan memandang bahwa pendekatan politik bisa dilakukan melalui dialog dengan gerakan DI/TII untuk menemukan konsensus dalam menyelesaikan masalah Aceh. Perdamaian di Aceh baru dapat dicapai setelah pemerintah pusat memutuskan untuk memberikan status Daerah Istimewa, yakni Aceh diberi hak khusus untuk mengatur masalah keagamaan, pendidikan, dan budaya